(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
Study was conducted in LHMC & Associated Smt Sucheta Kriplani Hospital New Delhi to estimate age from central maxillary incisor by calculating the index value of attrition. Total number of cases studied was one hundred and fifty. The objectives of the study were to evaluate the degree of attrition as objectively as possible, neutralizing the role of oral pathology and its correlation with age.